Pengembangan Media Board Game VOKUBA (Volume Kubus dan Balok) pada Pembelajaran Matematika Kelas V Sekolah Dasar - Drestanta, Inggita Nindya; Nelvita, Arda Wahyu; Priskasari, Anggi Destiana; Latifa, An-Nisa Khairi; Novianto, Anwar (Universitas Muhammadiyah Magelang, 2025)
This study was motivated by the difficulty of students in understanding concepts and linking new concepts with previously learned concepts, as well as the boredom of students in learning mathematics at SD Muhammadiyah Ngijon 1. This study aims to develop game-based learning media in the form of a VOKUBA (Volume of Cubes and Beams) Board Game. The type of research conducted is education and development research (R&D) with the ADDIE model, the data collection techniques used are observation, interview, and questionnaire. The data analysis technique used is qualitative descriptive analysis. The results of the analysis on media and material expert validation received a score of 96.75% Furthermore, the results of the VOKUBA Board Game media practicality test on teachers and students received a score of 90%. Based on these results, it can be concluded that the material and media packaged in the VOKUBA Board Game media are in the “Very Feasible” category, and based on the conversion guidelines for the practicality test of the VOKUBA Board Game media are included in the “Very Practical” category.